Apreciación de los empleadores de las organizaciones del sector industrial del departamento del Quindío sobre la calidad de la formación y el desempeño de los egresados del Programa de Contaduría Pública de la Universidad del Quindío. (2014)
It is necessary to mention the general laws that establish guidelines for higher education, such as Law 30 of 1992, which defines the character and autonomy of institutions of Higher Education-IES-, the object of academic programs and procedures building, inspection and monitoring of education; meanwhile, the quality conditions that higher education should be established by Decree 2566 of 2003 and Law 1188 of 2008, the decree regulated the conditions of quality and other requirements for the offering and development of academic programs in higher education , a rule that was repealed with the Law 1188 of 2008 which established a compulsory quality conditions for the qualified academic program registration, for which the higher education institutions, and demonstrate compliance with conditions of quality of programs must demonstrate certain conditions of institutional quality. It is for this reason that the public accounting program will meet the standards of control and supervision established by those entities. This program has been working for various activities to achieve re-accreditation of high quality, in order to form highly competitive professionals and project an image of the university charity Quindio, valuing the good name of the academic program and the institution